Microbial community characteristics of the intestine and gills of medium-form populations of Sthenoteuthis oualaniensis in the South China Sea - Hu, Xiaojuan; Su, Haochang; Zhang, Peng; Chen, Zuozhi; Xu, Yu; Xu, Wujie; Li, Jie; Wen, Guoliang; Cao, Yucheng (Frontiers in Marine Science, 2022)
Sthenoteuthis oualaniensis (purpleback squid) is an excellent biological resource in the South China Sea. However, the microbiological characteristics of this South China Sea squid, especially those of the medium-form of different sexes and gonadal maturities, are poorly understood. In this study, the bacterial community characteristics of the intestinal and gill tissues of female and male S. oualaniensis with different gonadal maturities, collected from the Nansha Sea of China in spring 2020, were analyzed. The results showed that Tenericutes, Proteobacteria, Firmicutes, and Bacteroidetes were the dominant phyla in the intestinal microbial samples of female immature gonad (FN), male immature gonad (MN), and male sexual maturity (MY) samples of the S. oualaniensis populations. Proteobacteria, Firmicutes, Bacteroidetes, and Tenericutes were the dominant phyla in the intestinal microbial sample of the female sexual maturity (FY) group. The microbial community in the gills differed from that of the intestinal flora. The dominant phyla in the gill samples were Proteobacteria, Firmicutes, and Bacteroidetes, regardless of sex or gonadal maturity. According to the random forest analysis, the gill samples had significantly (p<0.001) more Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways in the top 20 than the intestinal samples. Correlation analysis showed that the mantle length of S. oualaniensis was significantly (p<0.05) negatively correlated with the abundance of Tenericutes, but significantly (p<0.01) positively correlated with Firmicutes and Bacteroidetes. The mantle length of FY was significantly (p<0.05) longer than that of the other types. The results indicated that the differences in the intestinal bacterial community were related to the growth and feeding characteristics of S. oualaniensis of different sexes and maturities.